Characteristics of a freezing nanosuspension drop in two different schemes - Miao, Yanming (2022)
Understanding the freezing mechanism of a complex fluid drop is of interest from both fundamental study and application viewpoints. Whereas a water drop is frozen into a peach-like crystal due to the volume expansion upon freezing, the shape of a frozen complex fluid drop is still mysterious. In this work, we investigate the freezing dynamics of a nanosuspension drop in two different schemes, i.e., sessile and deposited. We find that the top of a frozen nanosuspension drop can either be a singular tip or flat plateau depending on the thermal condition onset of icing nucleation. Illustrated using a Hele-Shaw cell experiment, we attribute such intriguing freezing behaviors to the interplay between nanoparticles and two types of ice, i.e., dendritic ice formed in the recalescence stage and planar ice formed in the isothermal stage. Specifically, microcells constructed by dendritic ice lead to the failure of global freezing segregation, which yields the formation of the flat plateau. The fundamental understanding and the ability to control the shape of a frozen complex fluid drop have numerous promising applications in additive manufacturing, microelectronic systems, and others.